Posthuman Data Production in Classroom Studies – A Research Machine put to Work - Stenliden, Linnéa; Martín-Bylund, Anna; Reimers, Eva (Reconceptualizing Educational Research Methodology, 2018)
This paper describes a methodological inquiry that explores ways of performing classroom studies, where posthuman theory and data production are plugged in to each other from the very outset of this effort. Posthuman theory insists on research practices that demand attention to materialities, research practices that seek to detach the investigations from human concerns and positionality, research practices that consider how data and researcher(s) are entangled producing each other and by that try to operationalize the ‘unself’ of the researcher(s). Hence, a research machine was constructed and put to work in one Physics classroom in an upper secondary school. Five researchers focused on various multiparty interactions, whilst attempting to background the interpersonal interactions. Subsequently, the research machine was plugged into different concepts and turned into workshops where changes in configurations became significant for emergences in the classroom. In this process the concept affraction emerged as an effort to map how material-semiotic processes become observable in classrooms. The work of the research machine points to possible ways of avoiding commonly privileged perspectives in classroom observations. This attempt to deconstruct boundaries between human and non-human and the human as a bounded non-porous subject may affect possibilities to produce research that aids what otherwise might be shadowed actions in classrooms.